Penguatan Literasi Humanistik Di Lingkungan Keluarga - Putu Ayu Septiari Dewi; I Komang Wisnu Budi Wijaya (Universitas Cokroaminoto Palopo, 2024)
The research aims to analyze efforts to strengthen humanistic literacy in the family environment. This research is classified as a literature review. The research procedures are literature collection, literature review, literature selection, literature content analysis, synthesis and drawing conclusions. The data analysis was carried out using content analysis techniques. The results are that humanistic literacy can be strengthened in the family environment for example by crating a democratic family environment, open-ended questions, collaborative experiences, communication ethics and emotional intelligence. The parents roles are as a motivator, role model and able to create a conducive family situation.